Meet Your New Overlords: How Digital Platforms Develop and Sustain Technofeudalism - Geddes, Katrina (The Columbia Journal of Law & the Arts, 2020)
Much has been written about the free speech quasi-jurisprudence being developed by social media platforms through content moderation policies unconstrained by constitutional limits. This Article focuses on a specific subset of that content moderation—namely, the takedown of user-generated content in the name of copyright enforcement. This Article argues that the unlimited power of online platforms to regulate access to user-generated content through antipiracy algorithms leads to three perverse outcomes. First, the removal of lawful content falsely flagged as “infringing” results in the suppression of legitimate speech and a reduction in the diversity of online discourse. Second, the erosion of lawful exceptions and limitations to copyright protection through algorithmic adjudication alters the fundamental social contract established by copyright legislation, displaces decades of carefully developed fair use jurisprudence, and transfers adjudicatory power from courts to corporations. Third, the monetization of user-generated content not by users, but by copyright owners (following the flagging of content as “infringing”), is symptomatic of a broader, systemic exploitation of users that is occurring on digital platforms, also known as “technofeudalism.”